Building a Blessing Pharmaceutical Business: The Application of Islamic Ethics in Buying and Selling Generic Drugs - Afid, Muhammad Arif Nur; Abidin, Zaenal; Kurniawan, Kurniawan (CV. Zabags Qu Publish, 2025)
This study discusses the application of Islamic business ethics in the practice of buying and selling generic drugs, by highlighting the principles of honesty (ṣidq), justice ('adl), and transparency (ṣafā). Through a descriptive qualitative approach, data was obtained from observations, interviews, and documentation in several pharmacies and distributors of generic drugs. The results show that although generic drugs have a more affordable price, there are still challenges in uneven distribution, lack of price transparency, and low public education about the effectiveness of generic drugs. In addition, unfair business competition and weak regulations also hinder the application of Islamic business ethics in the pharmaceutical sector. Therefore, efforts are needed such as increasing information transparency, strengthening government policies, and internalizing Islamic ethical values in pharmaceutical business practices to create a fairer, more transparent, and blessed generic drug trade for all parties.